Cell-Penetrating Botulinum Neurotoxin Type A With Improved Cellular Uptake and Therapeutic Index - Wei, Xuan; Li, Lu; Wu, Yiwen; Liu, Jia (Frontiers in Bioengineering and Biotechnology, 2022)
Botulinum neurotoxin serotype A (BoNTA) is widely used for treating neuromuscular disorders. Despite of the various marketed products, BoNTA is known to have small therapeutic index ranging from 5 to 15. In the present study, we designed and characterized engineered BoNTA proteins with fusion of cell-penetrating peptides (CPPs). We have shown that CPPs, particularly a recently reported zinc finger protein (ZFP), could improve the cellular uptake and intramuscular therapeutic index of BoNTA. Our study has shed the light on developing next-generation neuromuscular modulators using CPP fusion.